Anomalous HZγ couplings in photon-induced collisions at the LHC - Senol, A.; Tasci, A. T.; Cakir, I. T.; Cakir, O. (World Scientific Pub Co Pte Lt, 2014)
We examined HZγ vertex and obtained the limits on anomalous aγ, bγ and [Formula: see text] couplings in a model-independent way through the γp collisions via the process pp→p γp→pHqX. The sensitivities to the anomalous couplings can be obtained as |bγ|, [Formula: see text] for the integrated luminosity of L int = 100 fb -1 at the LHC with [Formula: see text].
Keywords: High Energy Physics - Phenomenology; High Energy Physics - Phenomenology (hep-ph); FOS: Physical sciences; 16. Peace & justice; 3. Good health